Acceleration responses of building modules during road transportation. (1st May 2020) - Innella, Filomena; Bai, Yu; Zhu, Zhihui
Highlights: Comprehensive understanding of accelerations of building modules in transportation. Statistical analyses to investigate the nature of vibrations for modules in transportation. Accelerations responses obtained in three vibration dimensions at different locations. Effects on accelerations considered from truck model and speed and road roughness. Scalable PSDs defined for road transportation of building modules. Abstract: Modular construction uses panelised and volumetric units that are manufactured and furnished in a factory and delivered for site assembly. Such units are often transported on trucks through different road conditions and damages have been identified after transportation in practices. As a result, the evaluation of acceleration responses becomes important to understand the performance of building modules during the transportation. In this work, an experimental study was conducted to quantify the accelerations that building modules are typically subjected to during road transportation. Accelerations of both truck trailer bed and building module were measured through tri-axial accelerometers during transportation along different routes in Australia, where building modules with different dimensions and weights were carried with a tri-axle semi-trailer or vessel carrier trailer. Effects associated with the acceleration direction and position, road roughness and speed, were explored based on power spectral density (PSD) and statistical analyses. Finally, PSD spectra are presented according to the speed and road type and compared with standard PSDs in literature for transportation of packaged goods. It is expected that Spectra obtained in the study may be used to calculate mechanical responses of building modules during the transportation phase.